Uncertainty about perceived inflation target and monetary policy - Aoki, Kōsuke 1969-; Kimura, Takeshi (Dt. Bundesbank, 2007)
We analyse the interaction between private agents' uncertainty about inflation target and the central bank's data uncertainty. In our model, private agents update their perceived inflation target and the central bank estimates unobservable economic shocks as well as the perceived inflation target. Underthose two uncertainties, the learning process of both private agents andthe central bank causes higher order beliefs to become relevant, and this mechanism is capable of generating high persistence and volatility of inflation even though the underlying shocks are purely transitory. We also findthat the persistence and volatility become smaller as the inflation target becomes more credible, that is, the private agents' uncertainty about inflation target (and hence the bank's data uncertainty) diminishes.
Zsfassung in dt. Sprache
Keywords: Konferenzschrift